Integrate or perish : challenges of the Caribbean Community : keynote address at Dies Natalis Anton de Kom University of Suriname - Ramphal, Shridath
Makes the plea that Caribbean integration and Caribbean unity cannot happen if regionalism is not the unwritten premise of every Governmment's agenda; not occasionally, but always.States that it should not be only in response to ad hoc problems, but as the basic environment of policy.